Industrialization of hybrid Si/III–V and translucent planar micro‐tracking modules. (21st December 2020) - Nardin, Gaël; Domínguez, César; Aguilar, Álvaro Fernando; Anglade, Laetitia; Duchemin, Mathilde; Schuppisser, David; Gerlich, Florian; Ackermann, Mathieu; Coulot, Laurent; Cuénod, Blaise; Petri, Delphine; Niquille, Xavier; et al.
Abstract: A tracking‐integrated hybrid micro‐concentrator module is presented that can harvest direct, diffuse, and albedo irradiance components. It uses biconvex 180× lens arrays to concentrate direct light on high‐efficiency III–V solar cells (29% module efficiency has been demonstrated outdoors on direct sunlight at Concentrator Standard Test Conditions) and a planar micro‐tracking mechanism to allow installation in static frames. Two architectures have been developed to harvest diffuse irradiance: (1) a hybrid architecture where the backplane is covered with monofacial or bifacial Si cells; (2) a translucent architecture where diffuse light is transmitted through the module for dual‐land‐use applications, such as agrivoltaics. Simulations show that the hybrid architecture provides an excess of yearly energy production compared to 20% efficiency flat‐plate photovoltaic (PV) module in all locations studied, including those with a low direct normal irradiance (DNI) content, and up to 38% advantage in high‐DNI locations. The use of bifacial heterojunction and interdigitated back‐contact Si cells has been explored for the glass–Si–glass backplane laminate to harvest albedo light. Bifacial gains modeled can boost energy yield by about 30% in the best scenario. We discuss the perspectives of the translucent modules for dual‐land‐use applications as well, such as integration in greenhouses for agriculture‐integrated PV (agrivoltaics). This architecture can provide up to 47% excess electricity compared to a spaced reference Si array that transmits the same amount of solar photosynthetically active radiation for crop production. The HIPERION consortium funded by the European H2020 program is making an intensive effort to take this technology to the industrial scale. Abstract : A static tracking‐integrated hybrid micro‐concentrator module is presented that can harvest direct, diffuse, and albedo irradiance components. A high‐efficiency CPV submodule (29% CSTC) is combined with a Si backplane to harvest diffuse irradiance and provide an energy gain up to 38% compared to standard Si. Alternatively, a translucent backplane can be used to transmit light through the module for dual‐land‐use applications, such as agrivoltaics, where tracking can provide dynamic control of the solar dose to optimize crop yields.